Ciprofol attenuates the isoproterenol-induced oxidative damage, inflammatory response and cardiomyocyte apoptosis - Yang, Yunzhao; Xia, Zhongyuan; Xu, Cheng; Zhai, Chunchun; Yu, Xi; Li, Siqi (Frontiers in Pharmacology, 2022)
Background and Purpose: Ciprofol (HSK3486), a novel 2,6-disubstituted phenol derivative, is a new intravenous anesthetic compound with a similar chemical structure to propofol. Animal studies have also shown that propofol plays a protective role in a variety of cardiovascular diseases, including myocardial infarction, myocardial ischemia-reperfusion injury and takotsubo syndrome. However, whether ciprofol exerts cardioprotective effects on myocardial infarction remains unclear. Thus, the aim of this work was to explore the potential cardioprotective mechanism of ciprofol on isoproterenol (ISO)-induced myocardial infarction. Experimental Approach: In the present study, male C57BL/6 mice were subjected to subcutaneous injection of ISO (100 mg/kg) for 2 consecutive days to induce experimental myocardial infarction. Herein, we found that ciprofol could inhibit the abnormal increase in myocardial injury enzymes, the area of myocardial infarction and cardiac dysfunction in ISO-treated mice. Ciprofol administration increased the activity of superoxide dismutase and reduced the levels of NADPH oxidase and malondialdehyde in ISO-treated hearts. Additionally, ciprofol administration markedly reduced the expression of pro-inflammatory cytokines and cardiomyocyte apoptosis. In an in vitro model, the results also confirmed that ciprofol could inhibit ISO-induced oxidative damage, the inflammatory response and cardiomyocyte apoptosis. Moreover, ciprofol can activate the sirtuin1 (Sirt1)/nuclear factor erythroid 2-related factor 2 (Nrf2) pathway and Sirt1 and Nrf2 inhibition almost abolished ciprofol-mediated cardioprotective effects. Interpretation: Ciprofol protects the heart against ISO-induced myocardial infarction by reducing cardiac oxidative stress, the inflammatory response and cardiomyocyte apoptosis.